Answer:
Answer for number 17.
Explanation:
Simplifying
6(x + 4) = 3(4x + -2)
Reorder the terms:
6(4 + x) = 3(4x + -2)
(4 * 6 + x * 6) = 3(4x + -2)
(24 + 6x) = 3(4x + -2)
Reorder the terms:
24 + 6x = 3(-2 + 4x)
24 + 6x = (-2 * 3 + 4x * 3)
24 + 6x = (-6 + 12x)
Solving
24 + 6x = -6 + 12x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12x' to each side of the equation.
24 + 6x + -12x = -6 + 12x + -12x
Combine like terms: 6x + -12x = -6x
24 + -6x = -6 + 12x + -12x
Combine like terms: 12x + -12x = 0
24 + -6x = -6 + 0
24 + -6x = -6
Add '-24' to each side of the equation.
24 + -24 + -6x = -6 + -24
Combine like terms: 24 + -24 = 0
0 + -6x = -6 + -24
-6x = -6 + -24
Combine like terms: -6 + -24 = -30
-6x = -30
Divide each side by '-6'.
x = 5
Simplifying
x = 5